Implementation of an intelligent building solution within an Australian residental aged care facility - Schaper, Louise; Lapins, M. (Festival of International Conferences on Caregiving, Disability, Aging and Technology, 2007)
This paper comprises a case study report on the implementation of an intelligent building solution at SwanCare Group. The paper discusses the technology and development process involved in transforming SwanCare into one of the most technologically advanced aged care facilities within Australia.The independent living units, residential care facilities and administration buildings are connected by an intelligent building framework using IP networking based communications and messaging. Residents are provided with high speed Internet access, Voice-over-IP telephony, security and video services, assistance call and nurse call, as well as options to monitor their wellbeing. The unobtrusive monitoring of electricity,lights, water or any number of digital devices alerts staff if there is irregular use, which may indicate that a resident requires assistance.The impetus for this development was recognition of the value and potential of technology to enhance lifestyle and improve quality of life, meet the needs and expectations of residents, and to improve the quality and safety of care. Additionally, the technology has delivered significant financial benefit to SwanCare in the form of operational savings and a return on investment.The paper identifies the key success factors and benefits associated with the implementation. The paper concludes with an overview of the research program to investigate the potential of the technology to improve wellness and quality of life; and to address, delay and perhaps prevent the functional and cognitive declines associated with ageing, allowing older adults to continue to live independently.